Taxation of Per Diem. Romanian Current Liabilities for Employers and Employees - Mihaela Tofan; Ana Maria Bercu (CES Working Papers, 2015)
The accession to EU opened new opportunities in the area of transnational services, by using Romanian employees abroad. The general principle of free movement of labor allowed the employers to send their workers in another member states, under the domestic working contract. The cost for the human capital in the home country in comparison with this cost in the destination country determined fiscal implication, which were not addressed immediately by legislation. Therefore, disputes on doctrinarian level and also in practice evolved until a precise change in the legal framework became mandatory. The paper analyses these changing of the regulation, showing the limits of the regulation in force.
Keywords: K22; K34; J62; 330; taxation; workers; mobility; free movement